Using Sequencing Cards to Explore Students’ Vocabulary in Junior High School - Efa Silfia (Jurnal Sains Sosio Humaniora, 2018)
This research is aimed to describe how sequencing card can improve students’ vocabulary at grade VII A of SMPN 2 Sungai Penuh Academic Years 2015/2016 and the factors that influenced the changes of Students’ Vocabulary by using sequencing cards. It is a classroom action research. It was carried out in Class VII A. The data were quantitative and qualitative data. The quantitative data was taken from a vocabulary test. While the qualitative data was taken from observation done by the collaborator, field note and students’ interview. From the result of the research, the researcher found there was also an improvement in students’ achievement. The mean score of 48.7 in test cycle 1 increased to 73.1 in test cycle 2. Thus, the result of the research showed that sequencing card could improve students’ vocabulary and it becomes one of the appropriate ways in teaching vocabulary.